Association of Cholecystectomy With Liver Fibrosis and Cirrhosis Among Adults in the USA: A Population-Based Propensity Score-Matched Study - Xie, Zhi-Qin; Li, Hong-Xia; Tan, Wen-Liang; Yang, Lei; Ma, Xiao-Wu; Li, Wen-Xin; Wang, Qing-Bin; Shang, Chang-Zhen; Chen, Ya-Jin (Frontiers in Medicine, 2021)
BACKGROUND AND AIMS: Cholecystectomy is the “gold standard” for treating diseases of the gallbladder. In addition, nonalcoholic fatty liver disease (NAFLD), liver fibrosis or cirrhosis, are major causes of morbidity and mortality across the world. However, the association between cholecystectomy and these diseases is still unclear. We assessed the association among US adults and examine the possible risk factors. Methods This cross-sectional study used data from 2017 to 2018 National Health and Nutrition Examination Survey, a population-based nationally representative sample of US. Liver fibrosis and cirrhosis were defined by median stiffness, which were assessed by transient elastography. Furthermore, patients who had undergone cholecystectomy were identified based on the questionnaire. In addition, Propensity Score Matching (PSM, 1:1) was performed based on gender, age, body mass index(BMI) and diabetes. RESULTS Of the 4497 included participants, cholecystectomy was associated with 60.0% higher risk of liver fibrosis (OR:1.600;95% CI:1.278-2.002), and 73.3% higher risk of liver cirrhosis (OR:1.733, 95% CI:1.076-2.792). After PSM based on age, gender, BMI group and history of diabetes, cholecystectomy was associated with 139.3% higher risk of LF (OR: 2.393;95% CI: 1.738-3.297), and 228.7% higher risk of LC (OR: 3.287, 95% CI: 1.496-7.218). CONCLUSIONS The present study showed that cholecystectomy is positively associated with liver fibrosis and cirrhosis in US adults. The discovery of these risk factors therefore provides new insights on the prevention of NAFLD, liver fibrosis, and cirrhosis.